Assisted Suicide in Switzerland: Clarifying Liberties and Claims. (21st October 2016) - Hurst, Samia A.; Mauron, Alex
Abstract: Assisting suicide is legal in Switzerland if it is offered without selfish motive to a person with decision‐making capacity. Although the 'Swiss model' for suicide assistance has been extensively described in the literature, the formally and informally protected liberties and claims of assistors and recipients of suicide assistance in Switzerland are incompletely captured in the literature. In this article, we describe the package of rights involved in the 'Swiss model' using the framework of Hohfeldian rights as modified by Wenar. After outlining this framework, we dissect the rights involved in suicide assistance in Switzerland, and compare it with the situation in England and Germany. Based on this approach, we conclude that in Switzerland, claim rights exist for those requesting suicide assistance, and for those who are considering providing such assistance, even though no entitlements exist toward suicide assistance. We then describe the implementation of the 'Swiss model' and difficulties arising within it. Clarifying these issues is important to understand the Swiss situation, to evaluate what features of it may or may not be worth correcting or emulating, and to understand how it can impact requests for suicide assistance in other countries due to 'suicide tourism'. It is also important to understand exactly what sets Switzerland apart from other countries with different legislations regarding suicide assistance.